HUBUNGAN KETERSEDIAAN PANGAN TINGKAT RUMAH TANGGA DAN PENGETAHUAN TERHADAP STATUS GIZI REMAJA PUTRI DI SMA N 4 PADANG - Dasril, Oktariyani; Destri, Vella; Zaimy, Silvi; Idaman, Meldafia; Moryanda, Rury (STIKES Syedza Saintika Padang, 2024)
Indonesia is currently still facing multiple nutritional problems, namely the problem of undernutrition and overnutrition with the risk of disease. The purpose of this study was to determine the relationship between household level food availability and knowledge on the nutritional status of adolescent girls at SMA N 4 Padang. This type of research is descriptive analytic with a cross sectional study design. The population in this study were students of class XI and XII as many as 384 students, while the sample was taken using a proportional stratified random sampling technique as many as 216 respondents. Data were analyzed by univariate and bivariate using Chi-Square test. The results showed that more than half (53.1%) of the respondents had poor nutritional status. More than half (63.4%) of respondents have unsafe food availability at the household level and more than half (65.7%) of respondents have low knowledge. There is a relationship between food availability at household level (p-value 0.002) and knowledge (p-value 0.000) on the nutritional status of adolescent girls at SMA N 4 Padang in 2022. Based on the results of the study, it can be concluded that there is a relationship between food availability at the household level and knowledge of the nutritional status of adolescent girls. This suggestion was requested through the principal and teacher staff in order to provide information about nutrition and the importance of nutritional status once every 3 months through BK. the school can provide posters in every class about health and nutritional status. Keywords: Nutritional Status, Household Level Food Availability, Knowledge